Sagrado/profano no trato do corpo e da saúde na metrópole negra: Salvador nos anos 1950/1970 - Nascimento, Vilma Maria do (2007)
The aim of this study is to comprehend the basic differences in different conceptions of health and sickness in Salvador from 1950 to 1970 between official and traditional medicine, which has an African component. The study wants to comprehend, in the ways of this traditional city, the main spaces and professional activities allowing the re-creation and revitalization of those cultural practices, such as the terreiros de candomblé, the collection of herbs, the trade of the products that are used in the rituals of the Afro-Brazilian religions. It also wants to comprehend the meanders of legal processes in the control of the conflicts that were emerging in the urban public scene. That network of relations made possible the existence of social ways of living that are very typical from Salvador and characterize the daily life of this city of African ancestry. That network left signs that allow to learn "ways and roots" of the black cultures of this expanding metropolis. Its tangible and sensible evidences are within the material and symbolic universe of the popular healing arts that are present in a city that is full of tensions that permeate its magic-religious horizon. The study emphasizes the cultural kaleidoscope of Salvador, which makes possible the existence of many official or "popular" therapies experimented by completely different social segments, regardless of their class, gender, culture or ethnic group. A perspective established in forms such as the press dealt with and interpreted ways of living and knowledge linked to the sacred in the city, following the example of experiences lived and shared by "prophets and miracle makers". The work with criminal proceedings, where the clash among prosecutors, defendants and witnesses made possible to establish a context of tense social relations, allowed to realize that the accusations extrapolated the "material" level and brought up a multicultural cartography of the city that had been kept invisible by the dominant sectors until then. Oral statements collected from 1998 were indispensable to study those experiences in the healing arts of benzedeiros, mães-de-santo and pais-de-santo, as those statements are essential in the understanding of the transmission process of that traditional knowledge, which is renewed and updated in the orality and the constant remake of rituals with symbolic and real effectiveness